SUSTAINING THE MOTHER TONGUE: INSIGHTS INTO WAIJEWA LANGUAGE MAINTENANCE AMONG MIGRANT WORKERS IN THE DENPASAR DIASPORA - Christmas Prasetia Ate (Universitas Negeri Surabaya, 2026)
Migrant workers are a social group that is vulnerable to changes in language practices due to the need to adapt to new environments. This study aims to describe the domains of language use, language attitudes, and the factors underlying the maintenance of the Waijewa language among migrant workers from Wewewa subdistrict, Southwest Sumba, who reside in Denpasar, Bali. The research employed a descriptive qualitative approach supported by quantitative data. The main instrument was a questionnaire distributed to 22 respondents originating from five districts in Wewewa. The collected data were analyzed descriptively by calculating tendencies of language use, attitudes, and the dominant factors contributing to language maintenance. The findings reveal that the Waijewa language remains strong in domestic domains, particularly in the home, boarding houses, and communication with family through social media. However, its use tends to decline in public domains, which are predominantly influenced by Indonesian and Balinese. In terms of attitudes, almost all respondents expressed positive views toward the Waijewa language, demonstrated pride in its use, and emphasized the importance of transmitting it to future generations. The most influential factors in language maintenance are family roles, solidarity within the Sumbanese community, and cultural identity. Social media also contributes significantly, while workplace rules or policies show little influence. This study highlights that the maintenance of the Waijewa language in migration contexts is primarily supported by the internal strength of its speech community. Accordingly, the research contributes to the understanding of language maintenance dynamics of minority languages amid migration and the dominance of majority languages in multilingual urban settings.